Resin composition, composite adhesive film, copper-clad plate and preparation and application thereof
By using a resin composition of modified thermoset polyphenylene ether and modified filler, combined with PTFE fiber cloth and plasma surface treatment technology, a polyphenylene ether-based copper clad plate with improved copper layer binding and dielectric properties was prepared, and the solution was solved In the prior art, the problem of insufficient dielectric performance and adhesion of PPO-based copper clad plates has achieved improvement in stability and performance in high-frequency circuit board applications.
Patent Information
- Application Number
- CN202411652473.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the dielectric properties of PPO-based copper clad plates are limited at high frequencies, and the adhesion between the copper foil and PTFE is poor, resulting in shedding or bubbling in high-frequency circuit board applications.
The resin composition using thermoset polyphenylene ether and modified filler is used to modify the thermoplastic polyphenylene ether through redistribution reaction and terminal hydroxylallylation, and the inorganic powder is surface modified by silane coupling agent, combined with PTFE fibers Using cloth and plasma surface treatment technology, composite adhesive films and polyphenylene ether-based copper clad plates with improved copper layer binding and dielectric properties were prepared.
While maintaining ultra-low dielectric constant and dielectric loss at high frequencies, the peel strength between the copper layer and the substrate is improved, ensuring the stability and application performance of the high-frequency circuit board.
Smart Images

Figure CN119505515A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-frequency and high-speed copper-clad laminate preparation, and in particular to a resin composition, a composite adhesive film, a copper-clad laminate, and preparation and application thereof. Background Art
[0002] At present, with the development of high-frequency communications, the quality requirements for copper clad laminates are getting higher and higher. Among the composite materials used for high-frequency and high-speed copper clad laminates, polytetrafluoroethylene (PTFE) and polyphenylene ether (PPO) have very excellent dielectric properties. Among them, PPO has halogen-free properties, so it is widely used in high-frequency and high-speed copper clad laminates.
[0003] The conventional method of PPO-based copper-clad laminates is to press PPO powder or PPO-based composite materials with copper foil. However, on the one hand, the dielectric properties of the obtained PPO-based copper-clad laminates at high frequencies are limited and cannot be used in the ultra-high frequency field; on the other hand, the adhesion between the copper foil and PTFE obtained by this process is poor, which is easy to cause shedding or bubbling during the PCB processing process, thus affecting the application of high-frequency circuit boards (PCBs).
[0004] For example, CN 118562277A discloses a method for preparing a high-frequency and high-speed polyphenylene ether composition / silicon dioxide composite substrate, using a polyphenylene ether composition as a matrix resin, adding hydrocarbon resin, a cross-linking agent, a curing agent, and using low-dielectric-constant silicon dioxide as a filling material, to obtain a composite substrate with a low dielectric constant (3.03) and a low dielectric loss (0.0022), which has a large number of additives, and the peel strength between the substrate and the copper foil is not disclosed, and the dielectric constant is still high. CN117777699A discloses a polyphenylene ether resin composition and its application, using a polyphenylene ether resin as a matrix, a cross-linking agent, and a flame retardant as additives to form a polyphenylene ether composition, to obtain a substrate with a high peel strength (1.23N / mm), and its dielectric constant (3.42) and dielectric loss (0.0035) are still high, resulting in limited application.
[0005] In summary, when copper coating is performed on PPO, there is still a defect that the copper layer bonding performance and dielectric performance cannot be improved simultaneously. Summary of the invention
[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a polyphenylene ether-based copper clad laminate with improved copper layer bonding performance and dielectric properties, a preparation method thereof and applications thereof.
[0007] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0008] In order to achieve the above invention objectives, the present invention provides a resin composition, which includes a thermosetting polyphenylene ether and a modified filler. The thermosetting polyphenylene ether is obtained by redistributing a thermoplastic polyphenylene ether and modifying the terminal hydroxyl groups by propylene, and the modified filler is obtained by surface modifying an inorganic powder using a double bond-containing silane coupling agent.
[0009] Preferably, the preparation steps of the thermosetting polyphenylene ether are as follows:
[0010] (a) 15 parts by weight of toluene solution and 9 parts by weight of thermoplastic polyphenylene ether (molecular weight 12600 g / mol) were stirred in an oil bath at 95° C. until the thermoplastic polyphenylene ether was completely dissolved, 4.5 parts by weight of bisphenol A were added and mixed uniformly, 0.36 parts by weight of benzoyl peroxide were added, stirred for 6 hours, cooled to room temperature, washed with excess methanol, filtered, and dried to obtain a low molecular weight polyphenylene ether (molecular weight 2000-4000);
[0011] (b) 6 parts by weight of the low molecular weight polyphenylene ether obtained in step (a) and 100 parts by weight of chlorobenzene are stirred in an oil bath at 70° C. until the low molecular weight polyphenylene ether is completely dissolved, 1.74 parts by weight of methacrylic anhydride are added and mixed, 1.40 parts by weight of 4-dimethylaminopyridine is added, stirred for 4 hours, cooled to room temperature, washed with excess methanol, filtered, and dried to obtain a thermosetting polyphenylene ether.
[0012] Preferably, the double bond-containing silane coupling agent is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0013] Preferably, the preparation steps of the modified filler are as follows:
[0014] 3 parts by weight of inorganic powder and 150 parts by weight of ethanol were mixed, 0.06 parts by weight of a silane coupling agent containing a double bond was added, the mixture was stirred at 60° C. for 2 hours, the solvent was removed by filtration, and the mixture was dried at 100° C. to obtain the modified filler.
[0015] Preferably, the inorganic powder is nano-silicon dioxide. Preferably, the particle size of the nano-silicon dioxide is 10-200 nm.
[0016] Preferably, the weight ratio of the thermosetting polyphenylene ether to the modified filler is (47.5-49.5): (1-2.5).
[0017] The present invention also provides a method for preparing the resin composition, which comprises the following steps: uniformly mixing the thermosetting polyphenylene ether and the modified filler with a solvent to obtain a low dielectric resin composition. The solvent is preferably an organic solvent, more preferably one or more of chlorobenzene, toluene, acetone, N,N-dimethylformamide, and tetrahydrofuran, and particularly preferably toluene. More preferably, the ratio of the weight of the solvent to the total weight of the thermosetting polyphenylene ether and the modified filler is 5:1.
[0018] The present invention also provides a composite adhesive film, which comprises the resin composition according to the present invention and a PTFE fiber cloth.
[0019] The present invention also provides a method for preparing the composite adhesive film, which comprises the following steps: performing plasma surface treatment on the PTFE fiber cloth, then immersing it in the resin composition, and obtaining the composite adhesive film through immersion pulling, drying and hot pressing.
[0020] Preferably, the thickness of the PTFE fiber cloth is 10-100 μm, more preferably 50-100 μm.
[0021] Preferably, the gas used in the plasma surface treatment includes one or more of H2, NH3, Ar, O2 or CF4.
[0022] More preferably, the gas used in the plasma surface treatment comprises a mixed gas of H2, CF4 and O2 in a volume ratio of (1-2.5):1:1, a gas flow rate of 30-80 mL / min, a power of 200-2000 W, and an absolute vacuum degree of ≤1×10 -6 Pa, the surface treatment temperature is 80-160°C, and the treatment time is 5-60min, preferably 5-30min.
[0023] Most preferably, the gas used in the plasma surface treatment is a mixed gas of H2, CF4 and O2, with a volume ratio of 2:1:1, a gas flow rate of 50 mL / min, a power of 300 W, and an absolute vacuum of 0.5×10 -6 Pa, the temperature is 120℃ and the treatment time is 30min.
[0024] The present invention also provides a polyphenylene ether-based copper clad laminate, which comprises the composite adhesive film according to the present invention.
[0025] Preferably, the polyphenylene ether-based copper-clad laminate comprises a first electroplated copper layer, a first vacuum-plated metal film layer, a first polyphenylene ether-based composite material layer, a PTFE fiber cloth layer, a second polyphenylene ether-based composite material layer, a second vacuum-plated metal film layer, and a second electroplated copper layer, which are sequentially laminated. The first polyphenylene ether-based composite material layer and the second polyphenylene ether-based composite material layer are both made of the resin composition according to the present invention.
[0026] The present invention also provides a method for preparing the polyphenylene ether based copper clad laminate, which comprises the following steps: sequentially subjecting the composite adhesive film to plasma surface treatment, metal film plating and copper electroplating to obtain the polyphenylene ether based copper clad laminate.
[0027] Preferably, the gas used in the plasma surface treatment includes one or more of H2, NH3, Ar, O2 or CF4.
[0028] More preferably, the gas used in the plasma surface treatment comprises a mixed gas of H2, CF4 and O2 in a volume ratio of (1-2.5):1:1, a gas flow rate of 30-80 mL / min, a power of 200-2000 W, and an absolute vacuum degree of ≤1×10 -6 Pa, the surface treatment temperature is 80-160°C, and the treatment time is 5-60min, preferably 5-30min.
[0029] Most preferably, the gas used in the plasma surface treatment is a mixed gas of H2, CF4 and O2, with a volume ratio of 2:1:1, a gas flow rate of 50 mL / min, a power of 300 W, and an absolute vacuum of 0.5×10 -6 Pa, the temperature is 120℃ and the treatment time is 30min.
[0030] Preferably, the metal film is deposited by physical vapor deposition, with a deposition power of 5-60 kW, preferably 10 kW, a temperature of 250°C, and an absolute vacuum of ≤1×10 -3 Pa, preferably 1×10 -3 Pa, the obtained film layer can be one or more of a copper film, a nickel film or a gold film, and is particularly preferably a copper film, and the film layer thickness is 100-300nm, preferably 100nm.
[0031] Preferably, the copper plating method includes chemical copper plating or electrolytic copper plating.
[0032] More preferably, the operating pH value of the electroplated copper layer is 1-3, preferably 1, and the current density is 1.9-2.3A / dm 2 , preferably 2A / dm 2 , the temperature is 20-25°C, preferably 21°C, and the thickness of the obtained copper layer is 3-35μm, preferably 35μm.
[0033] The invention also provides application of the resin composition in a polyphenylene ether-based copper-clad laminate.
[0034] The invention also provides application of the composite adhesive film in a polyphenylene ether-based copper-clad laminate.
[0035] The present invention also provides application of the polyphenylene ether-based copper-clad laminate in a high-frequency circuit board.
[0036] The present invention utilizes modified silicon dioxide and double bonds on modified PPO molecular chains to carry out chemical reactions, greatly improving the compatibility between composite material interfaces and the uniformity of fillers in a matrix. The adhesive film obtained by impregnating, pulling, baking and hot pressing PTFE fiber cloth has excellent dielectric properties. The surface of the PPO-based adhesive film is activated by a plasma surface treatment process, and then a metal thin layer is deposited on the surface to cooperate with the activation phase to achieve an improvement in the bonding force between the copper-plated layer and the PPO-based adhesive film, so that the PPO-based copper-clad laminate obtained after the copper-plated layer still has good dielectric properties.
[0037] Compared with the prior art solutions, the thickness uniformity of the polyphenylene ether copper-clad laminate provided by the present invention is good, and it is possible to realize that PPO-based copper-clad laminates are maintaining ultra-low dielectric constant and dielectric loss performance while realizing high peel strength of PPO copper-clad laminates. Thermoplastic PPO is modified into low molecular weight thermosetting PPO using redistribution reaction and terminal hydroxyl allylation reaction, and then by the surface modification of silicon dioxide, the compatibility of filler and resin matrix can be effectively enhanced, and the uniformity of composite slurry is greatly improved, and PTFE fiber cloth is developed together with slurry after surface treatment, and the dielectric properties of PPO adhesive film can be greatly improved. After the adhesive film is subjected to plasma treatment, its surface can be activated, CO bond and -OH bond are bonded, and then the metal molecules of the film layer can be made to form chemical bonds (OX, X is nickel (Ni), copper (Cu), gold (Au)) with the PPO film surface after plasma treatment by vacuum coating treatment, so as to greatly improve the bonding performance of PPO adhesive film and copper foil. In addition, by combining physical vapor deposition and electroplating processes, thin copper layers of different thicknesses can be developed, which is conducive to the development of ultra-thin high-frequency and high-speed copper clad laminates. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic structural diagram of a novel polyphenylene ether-based copper clad laminate according to the present invention.
[0039] In the figure, the reference numerals are as follows: 1-electroplated copper layer, 2-vacuum plated metal film layer, 3-polyphenylene ether-based composite material layer, 4-PTFE fiber cloth layer. DETAILED DESCRIPTION
[0040] In order to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention, rather than to limit the scope of the present invention.
[0041] The present invention provides a resin composition, which includes a thermosetting polyphenylene ether and a modified filler, wherein the thermosetting polyphenylene ether is obtained by redistributing a thermoplastic polyphenylene ether and modifying the terminal hydroxyl groups by propylene, and the modified filler is obtained by surface-modifying a low-dielectric inorganic powder by using a silane coupling agent containing a double bond. The low-dielectric resin composition can be obtained by uniformly mixing the thermosetting polyphenylene ether and the modified filler through a solution.
[0042] The silane coupling agent containing double bonds includes, but is not limited to, one or more of vinyltrimethoxysilane, vinyltriethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
[0043] The inorganic powder may be nano-silicon dioxide, and the particle size may be 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.
[0044] The present invention also provides a composite adhesive film, which comprises the above resin composition and PTFE (polytetrafluoroethylene) fiber cloth. The preparation method of the composite adhesive film is: after the PTFE fiber cloth is subjected to plasma treatment, it is immersed in the resin composition, and then pulled, baked, and hot-pressed to obtain a low-dielectric composite adhesive film.
[0045] Specifically, the gas used in the plasma surface treatment includes one or more of H2, NH3, Ar, O2 or CF4. Exemplarily, the combination of gases used in the plasma surface treatment can be selected as: a combination of H2, NH3 and Ar; a combination of NH3, Ar and O2; a combination of Ar, O2 and CF4; a combination of H2, NH3, Ar and O2.
[0046] In the present invention, when the gas used in the plasma surface treatment includes H2, CF4 and O2 in a volume ratio of (1-2.5):1:1, the plasma surface treatment effect can be significantly improved, the bonding effect can be significantly improved, and at the same time, it can further ensure that the obtained product has good dielectric properties.
[0047] Specifically, the flow rate of the gas used in the plasma surface treatment can be 30-80 mL / min, for example, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min or 80 mL / min, etc., but not limited to the listed values, and other values not listed in this range also meet the requirements. The power of the plasma surface treatment can be 200-2000 W, for example, 200 W, 400 W, 600 W, 800 W, 1000 W, 1200 W, 1400 W, 1600 W, 1800 W or 2000 W, etc., but not limited to the listed values, and other values not listed in this range also meet the requirements. The absolute vacuum degree of the plasma surface treatment is ≤1×10 -6 Pa, for example, can be 1×10 -6 Pa, 0.9×10 -6 Pa, 0.8×10 -6 Pa, 0.7×10 -6 Pa, 0.6×10 -6 Pa, 0.5×10 -6 Pa, 0.4×10 -6 Pa, 0.3×10 -6 Pa, 0.2×10 -6 Pa or 0.1×10 -6 Pa, etc., but not limited to the listed values, and other values not listed in this range also meet the requirements. The temperature of the plasma surface treatment can be 80-160°C, for example, 80°C, 100°C, 120°C, 140°C or 160°C, etc., but not limited to the listed values, and other values not listed in this range also meet the requirements. The time of the plasma surface treatment can be 5-30min, for example, 5min, 10min, 15min, 20min, 25min or 30min, etc., but not limited to the listed values, and other values not listed in this range also meet the requirements.
[0048] Specifically, the thickness of the PTFE fiber cloth can be 10-100 μm, for example, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm or 100 μm, etc., but is not limited to the listed values, and other values not listed within the range also meet the requirements. In the present invention, the PTFE fiber cloth used is the original PTFE material or the modified PTFE material, which does not affect the realization of the effect of the present invention. For example, the PTFE is modified to improve the corresponding dielectric properties or bonding properties, which does not affect the improvement of the dielectric properties and bonding properties of the PTFE material body after being treated by the method of the present invention.
[0049] The present invention also provides a polyphenylene ether-based copper-clad laminate, which includes the composite adhesive film. The preparation method of the polyphenylene ether-based copper-clad laminate is as follows: subjecting the composite adhesive film to plasma treatment, physical vapor deposition metal film plating, and copper electroplating to obtain a copper-clad laminate.
[0050] The metallized film includes but is not limited to one or more of a copper film, a nickel film or a gold film. Specifically, the metallized film is deposited by physical vapor deposition. The deposition power of the metallized film can be 5-60kW, for example, 5kW, 10kW, 15kW, 20kW, 25kW, 30kW, 35kW, 40kW, 45kW, 50kW, 55kW or 60kW, but is not limited to the listed values. Other values not listed in this range also meet the requirements. The absolute vacuum degree of the metallized film is ≤1×10 -3 Pa, for example, can be 1×10 - 3 Pa, 0.8×10 -3 Pa, 0.6×10 -3 Pa, 0.4×10 -3 Pa, 0.2×10 -3 Pa or 0.1×10 -3 Pa, etc., but not limited to the listed values, and other values not listed in the range also meet the requirements. Specifically, the thickness of the film layer obtained by plating the metal film can be 100-300nm, for example, it can be 100nm, 150nm, 200nm, 250nm or 300nm, etc., but not limited to the listed values, and other values not listed in the range also meet the requirements.
[0051] Specifically, the relevant parameters of copper plating in the electroplated copper layer are selected according to the conventional requirements in the field to ensure that the thickness limit of the copper plating layer can be achieved. The plating solution used in the electroplated copper layer is selected according to the conventional requirements in the field to ensure that the thickness limit of the copper plating layer can be achieved. The operating pH value of the electroplated copper layer can be 1-3, for example, it can be 1, 1.5, 2, 2.5 or 3, but it is not limited to the listed values, and other values not listed in this range also meet the requirements. The current density of the electroplated copper layer can be 1.9-2.3A / dm 2 , for example, it can be 1.9A / dm 2 , 2A / dm 2 , 2.1A / dm 2 , 2.2A / dm 2 or 2.3A / dm 2The temperature of the electroplated copper layer can be 20-25°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, but is not limited to the listed values, and other values not listed in the range also meet the requirements. The thickness of the copper layer obtained by the electroplated copper layer can be 3-35μm, for example, 3μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm or 35μm, but is not limited to the listed values, and other values not listed in the range also meet the requirements.
[0052] Example
[0053] Further, in order to illustrate the bonding effect and dielectric properties that can be achieved by the polyphenylene ether-based copper clad laminate obtained by the preparation method provided by the present invention, the following actual examples are used for illustration, as follows:
[0054] The following polyphenylene ether powder (S201, Mn = 12600 g / mol) was purchased from Asahi Kasei Industries, Japan; toluene, chlorobenzene, methanol, bisphenol A, benzoyl peroxide, methylvinylsilane, methacrylic anhydride, ethanol and other reagents were purchased from Shanghai Aladdin Chemical Reagent Co., Ltd.
[0055] The electrolyte composition used in the following copper electroplating layers includes:
[0056] Anhydrous copper sulfate 120g / L, sulfuric acid 190g / L, Cl - 65ppm, AM-108 (purchased from Kunshan Hongqi Trading Co., Ltd.) 14mL / L and AM-108B (purchased from Kunshan Hongqi Trading Co., Ltd.) 0.5mL / L.
[0057] Other reagents and experimental instruments are commercially available in the art.
[0058] Example 1
[0059] 1. Preparation of low dielectric composite resin composition
[0060] (1) Preparation of thermosetting polyphenylene ether
[0061] (a) 15 parts by weight of toluene and 9 parts by weight of thermoplastic polyphenylene ether (molecular weight 12600 g / mol) are stirred in a 95° C. oil bath until the thermoplastic polyphenylene ether is completely dissolved, 4.5 parts by weight of bisphenol A are added and mixed uniformly, 0.36 parts by weight of benzoyl peroxide (BPO) are added, stirred for 6 hours, cooled to room temperature, washed with excess methanol, filtered, and dried to obtain a low molecular weight polyphenylene ether with a molecular weight of 2000-4000. In this step, the addition of BPO and bisphenol A will cause the polyphenylene ether molecules to break and rearrange to form a small molecular structure, thereby reducing the molecular weight of the polyphenylene ether.
[0062] (b) 6 parts by weight of the low molecular weight polyphenylene ether obtained in step (a) and 100 parts by weight of chlorobenzene are stirred in an oil bath at 70° C. until the low molecular weight polyphenylene ether is completely dissolved, 1.74 parts by weight of methacrylic anhydride are added and mixed, 1.40 parts by weight of 4-dimethylaminopyridine is added, stirred for 4 hours, cooled to room temperature, washed with excess methanol, filtered, and dried at 100° C. for 6 hours to obtain a thermosetting polyphenylene ether.
[0063] (2) Surface modification of nano-silica
[0064] 3 parts by weight of nano-silica (particle size of 15 nm) were mixed with 150 parts by weight of ethanol, 0.06 parts by weight of methylvinyldimethoxysilane was added, the mixture was stirred at 60° C. for 2 hours, the solvent was filtered out, and the mixture was dried at 100° C. to obtain modified nano-silica.
[0065] (3) Preparation of composite glue
[0066] 47.5 parts by weight of the thermosetting polyphenylene ether obtained in step (1) above was mixed with 250 parts by weight of toluene, and 2.5 parts by weight of the modified nano-silicon dioxide obtained in step (2) above was added, and stirred for 3 hours until the mixture was uniformly mixed to obtain a low dielectric composite resin composition.
[0067] 2. Preparation of composite film
[0068] The PTFE fiber cloth (thickness of 50 μm) was subjected to plasma surface treatment, and then immersed in the above-mentioned low dielectric composite resin composition, and a low dielectric composite adhesive film was obtained through immersion pulling, drying, and hot pressing.
[0069] 3. Preparation of polyphenylene ether based copper clad laminate
[0070] The composite adhesive film is sequentially subjected to plasma treatment, metal film plating and copper electroplating to obtain a polyphenylene ether-based copper-clad laminate.
[0071] The gas used in the plasma surface treatment was a mixture of H2, CF4 and O2 with a volume ratio of 2:1:1, a gas flow rate of 50 mL / min, a power of 300 W, and an absolute vacuum of 0.5×10 -6 Pa, the temperature is 120℃ and the treatment time is 30min.
[0072] The metal film was deposited by physical vapor deposition with a deposition power of 10 kW, a temperature of 250 °C, and an absolute vacuum of 1 × 10 -3 Pa, the obtained film layer is a copper film with a film thickness of 100nm.
[0073] The operating pH value of the electroplated copper layer is 1 and the current density is 2A / dm 2, the temperature was 21°C, and the thickness of the obtained copper layer was 35 μm.
[0074] The multilayer structure of the obtained polyphenylene ether based copper clad laminate is as follows Figure 1 The polyphenylene ether-based copper-clad laminate has a multi-layer composite structure, which includes an electroplated copper layer 1, a vacuum-plated metal film layer 2 (for example, a copper mold), a polyphenylene ether-based composite material layer 3, a PTFE fiber cloth layer 4, a polyphenylene ether-based composite material layer 3, a vacuum-plated metal film layer 2 (for example, a copper mold), and an electroplated copper layer 1.
[0075] Example 2
[0076] 1. Preparation of low dielectric composite resin composition
[0077] (1) Preparation of thermosetting polyphenylene ether
[0078] Same as Example 1.
[0079] (2) Surface modification of nano-silica
[0080] The coupling agent used was replaced by an equal amount of methylvinyldiethoxysilane instead of methylvinyldimethoxysilane, and other reagents and processing step condition parameters were the same as those in Example 1.
[0081] (3) Preparation of composite glue
[0082] 49.5 parts by weight of the thermosetting polyphenylene ether obtained in step (1) above was mixed with 250 parts by weight of toluene, and 0.5 parts by weight of the modified nano-silicon dioxide (15 nm) obtained in step (2) above was added, and stirred for 3 hours until the mixture was evenly mixed to obtain a low dielectric composite resin composition.
[0083] 2. Preparation of composite film
[0084] The thickness of PTFE is 80 μm. Other processing step conditions and parameters are the same as those in Example 1.
[0085] 3. Preparation of polyphenylene ether based copper clad laminate
[0086] Same as Example 1.
[0087] Example 3
[0088] 1. Preparation of low dielectric composite resin composition
[0089] (1) Preparation of thermosetting polyphenylene ether
[0090] Same as Example 1.
[0091] (2) Surface modification of nano-silica
[0092] The coupling agent used was replaced by an equal amount of vinyltriethoxysilane instead of methylvinyldimethoxysilane. Other reagents and processing step condition parameters were the same as those in Example 1.
[0093] (3) Preparation of composite glue
[0094] 49 parts by weight of the thermosetting polyphenylene ether obtained in the above step (1) was mixed with 250 parts by weight of toluene, and 1.0 parts by weight of the modified nano-silicon dioxide (15 nm) obtained in the above step (2) was added, and stirred for 3 hours to mix evenly to obtain a low dielectric composite resin composition.
[0095] 2. Preparation of composite film
[0096] The thickness of PTFE is 100 μm. Other processing step conditions and parameters are the same as those in Example 1.
[0097] 3. Preparation of polyphenylene ether based copper clad laminate
[0098] Same as Example 1.
[0099] Comparative Example 1
[0100] The only difference from Example 1 is that no nano silicon dioxide is added.
[0101] Comparative Example 2
[0102] The only difference from Example 1 is that the nano-silicon dioxide is not modified.
[0103] Comparative Example 3
[0104] The only difference from Example 1 is that no PTFE fiber cloth is added.
[0105] Comparative Example 4
[0106] The only difference from Example 1 is that the composite film is not subjected to plasma treatment, but is directly plated with copper.
[0107] Comparative Example 5
[0108] The only difference from Example 1 is that after the composite film is plasma treated, a layer of 35 μm copper foil is added to the upper and lower surfaces respectively, and then high-temperature pressing (pressure of 3 MPa, pressing temperature of 370° C., pressing time of 120 min) is performed to obtain a polyphenylene ether-based copper clad laminate.
[0109] The polyphenylene ether based copper clad laminates obtained in Examples 1-3 and Comparative Examples 1-5 were tested for dielectric constant and dielectric loss according to IEC 61189-2-721 (2015-04) standard at a frequency of 10 GHz; the peel strength was tested according to IPC-TM-650 2.4.8 standard, and the results are shown in Table 1.
[0110] Table 1
[0111] Dielectric constant (Dk) @ 10GHz Dielectric loss (Df) @ 10GHz Peel strength (N / mm) Example 1 2.24 0.0020 2.55 Example 2 2.50 0.0021 2.58 Example 3 2.40 0.0022 2.56 Comparative Example 1 2.90 0.0025 2.45 Comparative Example 2 2.70 0.0033 2.0 Comparative Example 3 3.10 0.0040 2.1 Comparative Example 4 2.35 0.0025 1.4 Comparative Example 5 2.35 0.0028 0.70
[0112] As shown in Table 1, compared with Examples 1-3 of the present invention, nano-silicon dioxide is not added in Comparative Example 1, and the dielectric properties of the film are not substantially improved, resulting in high dielectric properties; in Comparative Example 2, nano-silicon dioxide is not surface modified, resulting in poor compatibility between the filler and the resin interface, uneven dispersion of the filler, large dielectric loss, and low peel strength; in Comparative Example 3, PTFE fiber cloth is not added, there is no supporting carrier, and PTFE with better dielectric properties cannot be used to reduce the dielectric properties of the film; in Comparative Example 4, the composite film is not plasma treated to activate its surface, and there is a lack of metal bonds such as -O-Cu between the metal film and the film, which affects the peel strength of the copper clad laminate; Comparative Example 5 does not have vacuum plating and electroplating processes, and directly presses the copper foil, and there is also no chemical bonding between the metal bond and the film, which makes the peel strength of the copper clad laminate low. It can be seen that the polyphenylene ether-based copper clad laminate provided by the present invention has both low dielectric loss and good peel strength.
[0113] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0115] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A resin composition comprising a thermosetting polyphenylene ether and a modified filler, wherein the thermosetting polyphenylene ether is obtained by subjecting a thermoplastic polyphenylene ether to a redistribution reaction and propylene modification of terminal hydroxyl groups, and the modified filler is obtained by subjecting an inorganic powder to surface modification using a double-bond-containing silane coupling agent.
2. The resin composition according to claim 1, characterized in that The preparation steps of the thermosetting polyphenylene ether are as follows: (a) 15 parts by weight of a toluene solution and 9 parts by weight of a thermoplastic polyphenylene ether are stirred in an oil bath at 95° C. until the thermoplastic polyphenylene ether is completely dissolved, 4.5 parts by weight of bisphenol A are added and mixed uniformly, 0.36 parts by weight of benzoyl peroxide are added, stirred for 6 hours, cooled to room temperature, washed with excess methanol, filtered, and dried to obtain a low molecular weight polyphenylene ether; (b) 6 parts by weight of the low molecular weight polyphenylene ether obtained in step (a) and 100 parts by weight of chlorobenzene are stirred in an oil bath at 70° C. until the low molecular weight polyphenylene ether is completely dissolved, 1.74 parts by weight of methacrylic anhydride are added and mixed, 1.40 parts by weight of 4-dimethylaminopyridine is added, stirred for 4 hours, cooled to room temperature, washed with excess methanol, filtered, and dried to obtain a thermosetting polyphenylene ether.
3. The resin composition according to claim 1, characterized in that The preparation steps of the modified filler are as follows: Mix 3 parts by weight of inorganic powder with 150 parts by weight of ethanol, add 0.06 parts by weight of a silane coupling agent containing a double bond, stir, filter to remove the solvent, and dry to obtain the modified filler; preferably, the silane coupling agent containing a double bond is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
4. The resin composition according to claim 1, characterized in that The weight ratio of the thermosetting polyphenylene ether to the modified filler is (47.5-49.5): (1-2.5).
5. The method for preparing the resin composition according to any one of claims 1 to 4, comprising the following steps: The thermosetting polyphenylene ether and the modified filler are uniformly mixed by a solvent to obtain the resin composition. 6 . A composite adhesive film comprising the resin composition according to claim 1 and a PTFE fiber cloth.
7. The method for preparing the composite adhesive film according to claim 6, comprising the following steps: The PTFE fiber cloth is subjected to plasma surface treatment, and then impregnated in the resin composition, and the composite adhesive film is obtained through impregnation, pulling, drying and hot pressing. A polyphenylene ether-based copper-clad laminate comprising the composite adhesive film according to claim 6.
9. The method for preparing the polyphenylene ether based copper clad laminate according to claim 8, comprising the following steps: The composite adhesive film is subjected to plasma surface treatment, metal film coating and copper layer electroplating in sequence to obtain the polyphenylene ether-based copper-clad laminate.
10. Use of the resin composition according to any one of claims 1 to 4, the composite adhesive film according to claim 6 in a polyphenylene ether-based copper-clad laminate, and the polyphenylene ether-based copper-clad laminate according to claim 8 in a high-frequency circuit board.
Citation Information
Patent Citations
Polyphenyl ether resin composition and application thereof
CN117777699A
Preparation method of high-frequency and high-speed polyphenyl ether composition / silicon dioxide composite substrate
CN118562277A